Alfred Mason Badger papers - Badger, Alfred Mason, 1808-1868.
Diary (1832-1836) documenting Badger's merchant and building contracting businesses in Georgetown, Washington, D.C., and Boston, Mass., and reflecting the growth of the nation's capital (1832-1833); letters from Badger to his family while on a trip in New England (1868); his obituary (1868); genealogies of the Badger family (1635-circa 1949), of the Beck family (1743-circa 1860), and of the Hamden family (1666-circa 1909); and a scrapbook of poems. Also includes Civil War letters from Badger's son, Frank Appleton Badger, 140th New York Volunteers, and from his nephew, Hamlet F. Richardson, 108th New York Volunteers, and photographs of the two soldiers.
In part, transcripts.
Merchant and building contractor, of Georgetown, Washington, D.C., Boston, Mass., and Rochester, N.Y.
Collection material in English.
Keywords: Badger, Frank Appleton, -- 1842-1864 -- Correspondence; Richardson, Hamlet Faxon, -- 1842- -- Correspondence; Badger family; Beck family; Hamden family; United States. -- Army. -- New York Infantry Regiment, 108th (1862-1865); United States. -- Army. -- New York Infantry Regiment, 140th (1862-1865); Construction industry -- Washington (D.C.); Construction industry -- Massachusetts -- Boston; Genealogy; Merchants -- Washington (D.C.); Merchants -- Massachusetts -- Boston; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History; Contractors; Merchants